On the carrier phase of the "planetary" noble gases: TEM, Raman, and stepped combustion data for acid‐resistant residues from the Saratov (L4) meteorite. (25th June 2018) - Fisenko, Anatolii V.; Verchovsky, Alexander B.; Shiryaev, Andrei A.; Semjonova, Luba F.; Averin, Alexey A.; Vasiliev, Alexander L.; Nickolsky, Maximilian S.
Abstract: Acid‐resistant residues (ARR) were separated from the Saratov (L4) meteorite with the aim to shed more light on the origin of the planetary noble gases (the Q‐gases) in meteorites and the nature of their carrier phase (Q‐phase). Eleven fractions were obtained by HCl and HCl+HF etching, ultrasonication, and subsequent density separation of the ARR in isopropanol and isopropanol+NaOH. Two aliquots of the fractions were also treated with H2 O2 and HNO3 to investigate any influence of the oxidizing agent on the Q‐gases retention. The separated ARR fractions have been analyzed for C, N, and noble gases using step combustion. Raman and TEM analyses of the carbonaceous phase structures have also been applied for some of the fractions. This appears to be one of the most detailed investigations of the ARR fractions so far. The important observation made for the ARR fraction studied by TEM is the presence of abundant curved graphene stacks with a variable number of layers. Significant amounts of single‐ and bilayer graphenes and nanosized chromite grains partly covered with graphene layers are also observed. The principal features of the Q noble gases in the studied ARR fractions are the following. (1) Elemental composition of the Q‐gases depends on the extraction protocol. The most interesting is that upon H2 O2 oxidation, the noble gases are retained in the sequence Xe<Ar≪He, while after HNO3 it is in the sequence He≪Xe<Ar. (2) The resistance of the Q‐phase against the thermochemical treatment is lower than for the graphite‐like phase. The results of the current work together with literature data suggest that nongraphitizing curved graphene‐like carbon sheets are the most plausible carrier of the Q‐gases.